The Effect of Plasma Nitridation on Surface Hardness of Titanium Alloy (Ti-6Al-4V) for Artificial Knee Joint Applications - Angga Yunis Prasetya; Darmanto Darmanto; Muhammad Dzulfikar (Journal of Biomedical Science and Bioengineering, 2021)
Nitriding has been carried out using plasma nitriding techniques for surface treatment of Titanium as a biomaterial component. The purpose of this study was to determine the effect of plasma nitriding on surface hardness that occurs in titanium. The material used is Titanium Alloy (Ti-6Al-4V) Grade 5 which is processed by plasma nitriding by varying nitrogen (N2) and argon (Ar) gases of (100% N2/0% Ar), (95% N2/5% Ar), (90% N2/10% Ar), (85% N2/15% Ar), (80% N2/20% Ar), and (75% N2/25% Ar), and temperature 400ºC, time 5 hours and a pressure of 1.6 bar. The test results show that the optimum hardness is found in the gas composition with a ratio of 95% N2: 5% Ar. Obtained a hardness of 371 HV/VHN or an increase of 159% of the raw material with hardness value of 143 HV/VHN